Relevance of Immune Infiltration and Clinical Outcomes in Pancreatic Ductal Adenocarcinoma Subtypes - Liu, Rong; Liao, Ya-Zhou; Zhang, Wei; Zhou, Hong-Hao (Frontiers in Oncology, 2021)
Purpose: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer with high heterogeneity and dismal survival rates. Tumour immune microenvironment plays a critical role in sensitive to chemotherapy and prognosis. Herein, we determined the relevance of the composition of tumour-infiltrating immune cells to clinical outcomes in PDACs, and evaluated these effects by molecular subtype. Experimental Design: Data of 1,274 samples from publically available datasets were collected. Molecular subtypes were predicted with support vector machine. 22 subsets of immune cells were estimated with CIBERSORTX. The associations between each cell subset and overall survival (OS), relapse free survival (RFS) and complete response (CR) to chemotherapy were evaluated, modelling cellular proportions as quartiles. Results: An immune-related cluster was identified with unsupervised hierarchical clustering of hallmark pathways. Of the immune cells investigated, M0 macrophages emerged as closely associated with worse OS (HR =1.23, 95% CI = 1.15–1.31, p=1.57×10-9) and RFS (HR = 1.14, 95% CI =1.04–1.25, p=2.93×10-3), regardless of molecular subtypes. The CD8+ T cells conferred favourable survival. The neutrophils conferred poor OS overall (HR=1.17, 95% CI=1.10-1.23, p=1.74×10-7) and within the classical subtype. In the basal-like subtype, activated mast cells were associated with worse OS. Consensus clustering revealed six immune subgroups with distinct survival patterns and CR rates. The higher expression of PD1 was associated with better OS. Conclusions: The immune cellular composition infiltrate in PDAC are likely to have effects on prognosis. Further exploration of the cellular immune response has the potential to identify candidates for immunotherapy.